Split Computing for Vehicle Detection in Smart Parking - Silva, Milena F.; Silva, Heitor H. da; Oliveira, Mateus C.; Senna, Carlos; Souza, Allan M. de; Borin, Juliana F.; Bittencourt, Luiz F. (Anais do Workshop de Computação Urbana (CoUrb), 2026)
The increasing complexity of deep learning models like YOLO challenges the capabilities of low-cost edge devices in smart parking systems. To address this gap, we propose a Split Computing architecture applied to vehicle detection, where the neural network is partitioned between an edge client and a central server. This design offloads intensive computation, reducing local inference time and resource usage while preserving model accuracy. We evaluated distinct partitioning configurations, assessing computational costs and communication latency. Results demonstrate the solution’s effectiveness, highlighting its scalability for multi-tenant environments and sustainability potential by enabling the repurposing of low-cost TV set-top boxes as functional edge nodes.